FIKIH KOMPREHENSIF: SEBUAH PENDEKATAN DALAM STUDI ISLAM - Zaleha, Zaleha (Journal Analytica Islamica, 2019)
Abstract: The study of Islamic law has always moved dynamically following the times, this is whatled to the study of Islamic law to be an interesting phenomenon for Muslim academics. In a moretechnical level Islamic law is identified with fiqh which also grows in conjunction with the growth ofIslamic religion. The law is formed from the laws of the Koran, from the various laws that come out ofthe prophet. As a fatwa against a case, or an award against disputes, or an answer to a question. Thecomplication of the Fiqh laws in the first period is formed from the laws of God and its Apostles, andthe source is the Koran and the Sunnah. Using the study’s approach to the library of the followingdescriptions will explain in detail the comprehensive jurisprudence as an approach to Islamic studies.Keywords: Jurisprudence, Comprehensive, Islamic studiesDAFTAR PUSTAKAAl- Darimi, Imam. Sunan al-Darimi, Juz II. Beirut: Dar al-Fikr, t. th.Ardiansyah, Pengaruh Mazhab Hanbali dan Pemikiran Ibnu Taimiyah dalam Paham Salafi, JurnalAnalytica Islamica, Vol. 2, No. 2 Juli Desember 2013.Al-Jauziyah Ibn Qayyim.,I’lamul Muwaqi’in an Rabbil ‘Alamin, Juz I.Dar al-Jail, t. th.Amin, Ahnad. Fajr al- Islam. Beirut: Dar al-Kitab al-Arobi, 1969.Amin, Ahmad. Duha Islam, al-Qahairah: Lajnah al-Ta’lif wa al-Tarjamah, 1952.Al-Qardlawy, Yusuf.Ijtihad Dalam Syari’at Islam. Jakarta: Bulan Bintang, 1987.AR, Hasbi, Perbandingan Mazhab. Medan: Naspar Djaja, 1985.Ash Shiddieqy, M. Hasbi.Pengantar Hukum Islam. Jakarta: Bulan Bintang, 1967._______________. Pengantar Hukum Islam. Jakarta : Bulan Bintang, 1957._______________. Sejarah dan Pengantar Ilmu Al Qur’an / Tafsir. Jakarta: Bulan Bintang, 1954.Aziz Dahlan, Abdul. Ensiklopedi Hukum Islam. Jakarta: Ichtiar Baru Van Hoeve, 1997.Bangun, Ahmad.Ringkasan Hukum Islam. Medan: Zai Grafika Publishing, 2010.Chalil Munawar.Biografi Empat Serangkai Imam Mazhab. Jakarta: Bulan Bintang, 1990.Exposito, Jhaon L.Ensiklopedi Oxford. Bandung: Mizan, 2002.Khallaf, Abdul Wahhab.Ilmu Ushul fiqh . Semarang: Dina Utama. 1994.Ma’luf, Luis.Al-Munjid fil Al-Lughah AL-‘Alam, Beirut: Daar Masyriq, 1986.Napitupulu, Dedi Sahputra. “Nilai-Nilai Pendidikan Pada Kisah Nabi Adam AS.” TADRIS: JurnalPendidikan Islam 12.2 (2017): 243-256.Supriyadi, Dedi.Sejarah Hukum Islam. Bandung: Pustaka Setia, 2006.Syafe’i, Rachmat. Ilmu Ushul Fiqh. Bandung: Pustaka setia, 2007.Syaltut, Mahmud.Islam Aqidah dan Syari’ah. Jakarta: Pustaka Amani Press, 1986.Syarifuddin, Amir.Ushul Fiqih. Jakarta: Logos Wacana Ilmu, 1977.Yahya, Mukhtar, fatcurrahman.Dasar-dasar Pembinaan Hukum Fiqih Islami, Bandung: Al Ma’rif, 1983.Yunus, mahmua, Mahmud. Kamus Arab Indonesia. Jakarta: Mahmud Yunus Wal Dzyrriyyah, 2010.Ramadhani, Muhammad Lutfie, Hasan Asari, Wahyuddin Nur Nasution, “Strategi Pe n d i d i k a nMuallim Al-Qurra danHuffaz Al-Qur’an di Pondok Pesantren Islam Al-Mukmin NgrukiSurakarta Jawa Tengah, dalam Jurnal At-Tazakki, Vol. III, No. 1, Tahun 2019.Sayyid Qutb, Hadha al-Din, Agama Islam, U.S.A: I.I.F.S.O. Publication, United. tt.Sipahutar, Romat Efendi, Mardianto, Wahyuddin Nur Nasution, “Model Pembelajaran Alquran diMAN 2 Model Medan, dalam JurnalEdu Religia, Vol.III, No 1, Tahun 2019.Siregar, Syaiful Azhar. “Penerapan Metode Takrir dan Muraja’ah dalam Pembelajaran Alquran diSD Yayasan Pendidikan Shafiyyatul Amaliyah Medan”, dalam Jurnal Edu Religia, Vol.III, No. 2, Tahun 2019, h. 248.Zulkarnaen, Syamsu Nahar dan Zulheddi, “Nilai-Nilai Pendidikan dalam Al- Qur’an Perspektif Surah‘Abasa, dalam Jurnal At-Tazakki, Vol. II, No. 2, Tahun 2018.